Hyperganglionosis mimicking Hirschsprung's disease. Issue 11 (November 1991) - Athow, A C; Filipe, M I; Drake, D P
Abstract : Three patients with hyperganglionosis are reported in whom an initial diagnosis of Hirschsprung's disease was suspected. In one patient there was a classic presentation with constipation, in another Hirschsprung's disease coexisted, and in the third the initial inadequate suction rectal biopsy specimen was suggestive of Hirschsprung's disease on acetylcholinesterase staining. Evidence of hypertrophy and hyperplasia of the intermuscular and submucosal plexuses on a full thickness bowel biopsy specimen was used to confirm the diagnosis of hyperganglionosis, suggested by the characteristic demonstration of moderate increase in the number of acetylcholinesterase stained nerve fibres in the lamina propria mucosae on rectal biopsy. Surgical management was guided by clinical signs. Two patients had colonic resections; the third had temporary stomal diversion. Hyperganglionosis is rarer than Hirschsprung's disease but is known to mimic it. We suggest full thickness bowel specimens are needed to confirm the diagnosis and that inadequate rectal suction biopsies must be interpreted with caution.